2015
DOI: 10.1038/nature14665
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of multipotency by oncogenic PIK3CA induces breast tumour heterogeneity

Abstract: Breast cancer is the most frequent cancer in women and consists of heterogeneous types of tumours that are classified into different histological and molecular subtypes. PIK3CA and P53 (also known as TP53) are the two most frequently mutated genes and are associated with different types of human breast cancers. The cellular origin and the mechanisms leading to PIK3CA-induced tumour heterogeneity remain unknown. Here we used a genetic approach in mice to define the cellular origin of Pik3ca-derived tumours and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
256
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(291 citation statements)
references
References 46 publications
(38 reference statements)
23
256
0
Order By: Relevance
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Further studies will determine whether the potential MYC-induced cell fate switch observed here bears similarities to recent discoveries of oncogene-induced cell fate conversions in lineage restricted subpopulations and whether it contributes to tumor heterogeneity in human breast cancer. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…However, we suggest that the pathophysiological role of Sox2 in melanoma can best be assessed in genetically engineered mouse melanoma models, in which melanoma spontaneously develops within an undisturbed stromal environment and without prior tumor cell isolation which might influence the cells' behavior. Importantly, Cancer formation has been associated with reactivation of embryonic or organ-specific stem cell programs 40,41 . Accordingly, Sox2 has been functionally implicated in several tumors emerging from tissues harboring Sox2-positive stem cells 1,31 .…”
Section: Sox2 Is Dispensable For Primary Tumor and Metastasis Formationmentioning
confidence: 99%